Rabbit Hemorrhagic Disease Virus Non-structural Protein 6 Induces Apoptosis in Rabbit Kidney Cells - Chen, Mengmeng; Liu, Xing; Hu, Bo; Fan, Zhiyu; Song, Yanhua; Wei, Houjun; Qiu, Rulong; Xu, Weizhong; Zhu, Weifeng; Wang, Fang (Frontiers in Microbiology, 2019)
Rabbit hemorrhagic disease (RHD) is a highly contagious disease caused by rabbit hemorrhagic disease virus (RHDV). Previous research has shown that RHDV induces apoptosis in numerous cell types, although the molecular mechanisms underlying the apoptosis induced by RHDV are not well understood. One possible factor is non-structural protein 6 (NSP6), a 3C-like protease that plays an important role in processing viral polyprotein precursors into mature non-structural proteins. To fully establish a role for NSP6, the present study examined the effects of ectopic expression of the protein in rabbit (RK13) and human (HeLa and HepG2) cells. We found that NSP6 suppressed cell viability and promoted apoptosis in all three cell types in a dose-dependent manner. We also identified increased caspase-3, -8, and -9 activities in RK13 cell, and an increased BAX to BCL2 mRNA ratio. Mechanistically, the ability of NSP6 to induce apoptosis was significantly impaired by mutation of the catalytic His27 residue, implying that this position is critical. Our study has shown that RHDV NSP6 can induce apoptosis in host cells and is likely an important contributor to RHDV-induced apoptosis and pathogenesis.